Slow gait speed – an indicator of lower cerebral vasoreactivity in type 2 diabetes mellitus - Jor’dan, Azizah J.; Manor, Brad; Novak, Vera (Frontiers in Aging Neuroscience, 2014)
Objective: Gait speed is an important predictor of health that is negatively affected by aging and type 2 diabetes. Diabetes has been linked to reduced vasoreactivity, i.e. the capacity to regulate cerebral blood flow in response to CO2 challenges. This study aimed to determine the relationship between cerebral vasoreactivity and gait speed in older adults with and without diabetes. Research design and methods: We studied 61 adults with diabetes (65±8yrs) and 67 without diabetes (67±9yrs) but with similar distribution of cardiovascular risk factors. Preferred gait speed was calculated from a 75m walk. Global and regional perfusion, vasoreactivity and vasodilation reserve were measured using 3-D Continuous Arterial Spin Labeling MRI at 3 Tesla during normo-, hyper- and hypocapnia and normalized for end-tidal CO2. Results: Diabetic participants had slower gait speed as compared to non-diabetic participants (1.05±0.15m/s vs. 1.14±0.14m/s, p< 0.001). Lower global vasoreactivity (r2adj=0.13, p=0.007), or lower global vasodilation reserve (r2adj=0.33, p< 0.001), was associated with slower walking in the diabetic group independently of age, BMI and hematocrit concentration. For every 1mL/100g/min/mmHg less vasodilation reserve, for example, gait speed was 0.05m/s slower. Similar relationships between vasodilation reserve and gait speed were also observed regionally within the cerebellum, frontal, temporal, parietal and occipital lobes (r2adj=0.27-0.33, p< 0.0001). In contrast, vasoreactivity outcomes were not associated with walking speed in non-diabetic participants, despite similar vasoreactivity ranges across groups. Conclusions: In the diabetic group, those with lower global vasoreactivity was associated with slower walking speed. Slower walking in older diabetic adults may hallmark reduced vasomotor reserve and thus the inability to increase perfusion in response to greater metabolic demands during walking.